Editorial: researching children's understandings of poverty and risk in Diverse Contexts - Crivello, G; Camfield, L; Porter, C (Blackwell Publishing Ltd., 2010)
Throughout the world, children experience and manage risk as a part of their everyday lives. But growing up poor may be a particular source of vulnerability and disadvantage for children, especially where they are confronted with gross inequalities. The global challenge is huge. By 2015, it is estimated that nearly one third of the world’s population will be under the age of fourteen. At the same time, children are disproportionately represented among the world’s poor. More than 30 per cent of children in developing countries – about 600 million – live on less than US $1 a day (UNICEF, 2008). In this special issue of Children & Society, we present eight papers focusing on children’s everyday experiences of poverty and risk in developing country contexts.